Inflated ordered outcomes - Brooks, R.; Harris, Mark; Spencer, C. (Elsevier, 2012)
We extend Harris and Zhao (2007) by proposing a (Panel) Inflated Ordered Probit model, and demonstrate its usefulness by applying it to Bank of England Monetary Policy Committee voting data.